APLIKASI SMS GATEWAY UNTUK MENINGKATKAN LAYANAN SISWA DI SMAN 1 CIBINGBIN BERBASIS OPERASIONAL CRM - Erlan Darmawan; Ade Nanang khozin (NUANSA INFORMATIKA, 2011)
CRM become one of the main factor in maintaining relation between company/organization with the member/customer. School is an educational institution that has many member (student). The implementation of CRM become the front line in keeping the communication between the school and the student, also the student’s parents, as it held in SMA Negeri 1 Cibingbin. However there are problems in implementing CRM. The problems occured because CRM operation in the school operated in conventional way which is based on paper. The using of paper in CRM implementation become less effective. There are many way to communicate, one of them is by using SMS. SMS also can be integrated to a system through a gateway.SMS gateway is a platform which provides mechanism of sending and receiving SMS form mobile device. Communication between school and student also student’s parent can be held through SMS gateway. With the using of SMS gateway could give a solution to solve the problem in CRM operation. Student and student’s parent could get the information that they want to know directly and specifically.Keyword : sms, gateway, service, php, mysql